The implications of process metaphysics for Christian mysticism - Breeding, Marshall M., author; Crosby, Donald A., advisor (Colorado State University. Libraries, 1982)
This study gives a metaphysical discussion of mystical Christianity, comparing and contrasting the traditional static metaphysics with a metaphysical scheme where process is fundamental. Two Christian mystics, Meister Eckhart and St. John of the Cross, are used to exemplify the pattern of life and traditional metaphysical outlook of Christian mysticism. Alfred North Whitehead’s metaphysical scheme, as presented in his Process and Reality, serves as the process alternative. For all three persons the doctrine of God provides the focus for metaphysical discussion. The principal aim of the metaphysical discussion is to argue that process metaphysics provides a more adequate interpretation for the experiences of the Christian mystics than the static, non-process metaphysics the mystics themselves used. The main characteristic of the mystics' experience which metaphysics must take into account is the intimacy the mystic feels with God. Eckhart interprets the intimacy through an ontological union which occurs on God's transcendent level of existence. St. John suggests that no ontological union occurs but that mystical experience is a volitional transformation. Whitehead's metaphysical categories do not allow for an ontological union but do provide a conception of God and a model of human experience where a very intimate relation is possible between the mystic and God. I argue that Whitehead's view of God as relative, changing, and interacting with the world, more adequately represents what the mystics experience than the view of God as non-relative, static, and metaphysically distinct from the world, which characterizes the theologies of the mystics themselves.
Department Head: P. L. McKee.
Keywords: St. John of the Cross; Meister Eckhart; process metaphysics; Whitehead, Alfred North; mystical Christianity; Christian mysticism; Mysticism; Metaphysics